Consumers' buying intention towards healthy foods during the COVID-19 pandemic in an emerging economy - Syed Shah Alam; Cheng-Kun Wang; Chieh-Yu Lin; Mohammad Masukujjaman; Yi-Hui Ho (Cogent Business & Management, 2022)
This study investigates the determinants of buying intention towards healthy foods in Malaysia through a modification of the theory of planned behavior. The moderating role of food safety trust is also analyzed in the study. Drawing on an online questionnaire survey from 375 respondents in Malaysia during the COVID-19 time, the empirical results revealed that food safety concern, health consciousness, nutritional content, attitude, and premium price, significantly affect buying intention. Food safety trust significantly moderates the relationship between buying intention and food safety concern, health consciousness as well as nutritional content. Implications and guidelines are discussed for the policy makers and practitioners. This study developed a model by integrating cognitive product-related factors along with TPB constructs. The findings of this article are of special value for public and private organizations to manage and market healthy foods during the COVID-19 pandemic era.
Keywords: 650; COVID-19; food safety trust; Healthy foods; theory of planned behavior